The rule of law strengthening on corporate green innovation: a quasi-natural experiment based on the establishment of environmental courts in China - Guo, Yujing; Liu, Nibing; Chang, Le; He, Hongguang (Frontiers in Environmental Science, 2024)
Strong judicial support is an important guarantee for a country’s environment to achieve good governance. This paper utilizes a multi-period difference-in-differences approach to examine the impact of environmental justice reform, represented by environmental tribunals, on corporate green innovation and its underlying mechanisms. It is found that environmental courts can effectively promote green innovation in enterprises, and their effect on “substantive green innovation” is more significant than that on “strategic green innovation”. The environmental court is divided into the environmental resources trial court and the environmental resources panel court, and the trial court has a more pronounced effect on promoting corporate green innovation than the environmental resources panel court. The establishment of environmental protection courts can improve the efficiency of regional environmental justice, enhance the government’s awareness of environmental protection, and increase the cost of illegal activities by enterprises, thereby promoting corporate green innovation. The promotion effect of environmental courts on corporate green innovation is more significant in regions with non-state-owned enterprises, better legal environments, and lower levels of industry competition. The main findings still hold after considering robustness tests, such as the endogeneity of environmental court establishment. The study suggests that environmental judicial specialization has a positive impact on corporate green innovation, and that the reform of environmental judicial specialization should be continuously deepened to provide useful insights for the construction of the ecological rule of law and the green transformation of enterprises.